Exploring the implications of the new ICD-10-CM classification system for injury surveillance: analysis of dually coded data from two medical centres. Issue Volume 27:Issue Suppl 1(2021) (9th April 2021) - Poltavskiy, Eduard A; Fenton, Susan H; Atolagbe, Oluseun; Sadeghi, Banafsheh; Bang, Heejung; Romano, Patrick S
Abstract : Introduction: External cause of injury matrices is used to classify mechanisms/causes of injuries for surveillance and research. Little is known about the performance of the Centers for Disease Control and Prevention's new external cause of injury matrix for Clinical Modification of the 10th Revision of the International Classification of Diseases (ICD-10-CM), compared with the ICD-9-CM version. Methods: Dually coded (ICD-9-CM and ICD-10-CM) administrative data were obtained from two major academic trauma centres. Injury-related cases were identified and categorised by mechanism/cause and manner/intent. Comparability ratios (CR) were used to estimate the net impact of changing from ICD-9-CM to ICD-10-CM on the number of cases classified to each mechanism/cause category. Chamberlain's percent positive agreements (PPA) were calculated and McNemar's test was used to assess the significance of observed classification differences. Results: Of 4832 and 5211 dual-coded records from the two centres, 632 and 520 with injury-related principal diagnoses and external cause codes in both ICD-9-CM and ICD-10-CM were identified. CRs for the mechanisms/causes with at least 20 records ranged from 0.85 to 1.9 at one centre and from 0.97 to 1.07 at the other. Among these mechanisms/causes, PPAs ranged from 33% for 'other transport' to 94% for poisoning at one centre, and from 75% for 'other transport' to 100% for fires/burns at the other centre. Case assignment differed significantly for falls, motor vehicle traffic, other transport, and 'struck by/against' injuries at one centre, and for 'other pedal cyclist' at the other centre. Conclusion: Switching to ICD-10-CM and the new external cause of injury matrix may affect injury surveillance and research, especially for certain mechanisms/causes.